Analisis Strategi Bisnis NPV, IRR, PI dan DPB pada Golden Restaurant Jakarta - Kriswanto, Kriswanto (Binus Business Review, 2011)
Golden Restaurant is located in Senayan, South Jakarta. Because of intense competition and a lack of good economic growth in Indonesia, the restaurant sales dropped sharply and having some problems in operation. The measures is to do effective business strategies to improve business performance by conducting research, create a budget to analyze and predict the financial performance, and formulate an effective working capital structure. Formulation of the problem discussed is NPV and IRR of restaurant sales for the feasibility of an investment, securities of the PI and IBA restaurant on the return on investment and analysis NPV, IRR, PI and IBA on strategy formulation restaurant. From the analysis of simple direct study expected an increase in sales to 90% per year and provide a significant positive NPV and IRR of almost 20% which is higher than the original expectation of 15% and reach breakeven point within 4 to 7 years. From the results of this analysis also shows the business is sensitive to increased sales, operating expenses and cost of sales. In addition to inflation and economic conditions affect the performance of sensitive business.